Enhanced Antitumor Efficacy through an "AND gate" Reactive Oxygen-Species-Dependent pH-Responsive Nanomedicine Approach - Jäger, Eliézer; Humajová, Jana; Dölen, Yusuf; Kučka, Jan; Jäger, Alessandro; Konefał, Rafał; Pankrác, Jan; Pavlova, Ewa; Heizer, Tomáš; Šefc, Luděk; Hrubý, Martin; Figdor, Carl G; et al. (Advanced healthcare materials, 2021)
Anticancer drug delivery strategies are designed to take advantage of the differential chemical environment in solid tumors independently, or to high levels of reactive oxygen species (ROS) or to low pH, compared to healthy tissue. Here, the design and thorough characterization of two functionalizable "AND gate" multiresponsive (MR) block amphiphilic copolymers are reported, aimed to take full advantage of the coexistence of two chemical cues-ROS and low pH-present in the tumor microenvironment. The hydrophobic blocks contain masked pH-responsive side chains, which are exposed exclusively in response to ROS. Hence, the hydrophobic polymer side chains will undergo a charge shift in a very relevant pH window present in the extracellular milieu in most solid tumors (pH 5.6-7.2) after demasking by ROS. Doxorubicin (DOX)-loaded nanosized "AND gate" MR polymersomes (MRPs) are fabricated via microfluidic self-assembly. Chemical characterization reveals ROS-dependent pH sensitivity and accelerated DOX release under influence of both ROS and low pH. Treatment of tumor-bearing mice with DOX-loaded nonresponsive and "AND gate" MRPs dramatically decreases cardiac toxicity. The most optimal "AND gate" MRPs outperform free DOX in terms of tumor growth inhibition and survival, shedding light on chemical requirements for successful cancer nanomedicine.
Keywords: cancer therapy; drug delivery; doxorubicin; lékové transportní systémy; micely; Oxygen; functional materials; multiresponsive polymers; reaktivní formy kyslíku; nanomedicína; Nanoparticles; nanočástice; Hydrogen-Ion Concentration; Drug Carriers; nanomedicine; koncentrace vodíkových iontů; Reactive Oxygen Species; Nanomedicine; Drug Delivery Systems; Animals; kyslík; Micelles; zvířata; myši; Mice; nosiče léků; Doxorubicin